THE IMPLEMENTATION OF COACHING AND MENTORING ON BASIC TRAINING FOR CIVIL SERVANT CANDIDATES (CPNS) IN RELIGIOUS EDUCATION AND TRAINING CENTER SEMARANG - Fatkhur Rohmah, Ana; Made Sudana, I; Prihatin, Titi (Educational Management, 2020)
This study examines the application of the Coaching and Mentoring Model to the Civil Servant Candidates? (CPNS) Basic Training at the Religious Education and Training Center Semarang. The objectives of study are to know (a) the application of the coaching and mentoring model for the preparation of the actualization report (b) the impact of the application of the model, and (c) the strengths and weaknesses of this Coaching and Mentoring model. The study uses a descriptive qualitative approach based on program evaluation. The data colected mainly through observation, intervews, and documentation. The results of this study indicate that the mentoring model for the preparation of proposals and actualization is carried out by coaches and mentors through learning, mentoring, and consulting. The impact is positive. There is a match between actualization with the needs of the institution, the ease of participants in preparing plans, implementation, and actualization report. As for the advantages of helping participants recognize the potential of the participants, the implementation is more flexible because the coach is the participant?s teacher and the mentor is the participant's immediate supervisor. The weaknesses is that there is no guidance book for both coaches and mentors so that both coaches and mentors lack coordination between coaches and mentors, less coaches mentoring to participants because of the number of coachee is a relatively large number, and there are different knowledge among the coaches, and lack of common perception among coaches in the preparation of actualization and reports.